Adam Smith's system : a re-interpretation inspired by Smith's lectures on rhetoric, game theory, and conjectural history /: a re-interpretation inspired by Smith's lectures on rhetoric, game theory, and conjectural history. (2022) - Ortmann, Andreas; Walraevens, Benoît
No abstract available